Initial Validation for the Assessment of Pragmatic Abilities and Cognitive Substrates (APACS) Hebrew Battery in Adolescents and Young Adults With Typical Development - Fussman, Shanie; Mashal, Nira (Frontiers in Communication, 2022)
Currently there is no validated battery to assess pragmatic abilities in Hebrew. The use of such battery has great importance, as it provides norms to the assessment of impaired pragmatic skills, within neurodevelopmental disorders, such as ASD, schizophrenia, learning disabilities, dyslexia and intellectual disabilities. In order to validate the battery, the Assessment of Pragmatic Abilities and Cognitive Substrates (APACS) was translated to Hebrew (Arcara & Bambini ,2016). The APACS battery was previously validated and found high reliability and validity for ages 19-89 years. The battery includes six tasks, focusing on two main domains: pragmatic production and pragmatic comprehension. The assessment of pragmatic production will be conducted by the use of interview and description tasks, whereas pragmatic comprehension will be assessed by narratives, two figurative language, and humor tasks. The translated battery, APACS-Heb is currently the most comprehensive and the first validated battery for pragmatic tests in Hebrew. Forty Hebrew-speaking adolescents ages 16-20 participated in the study. All participants performed screening tests assessing vocabulary, Theory of Mind and social responsiveness. In addition, the validity and test-retest reliability of APACS-Heb were assessed. Furthermore, the effect of vocabulary, Theory of Mind and social responsiveness on performance was evaluated. High internal consistency, content validity and test-retest reliability was found for most APACS-Heb tasks and all composite scores. Furthermore, an effect of age and gender was found for most tasks with females outperformed males. In addition, a contribution of Theory of Mind to pragmatic production, pragmatic comprehension and APACS total scores was found. Lastly, a factor analysis revealed two factors, in which the first factor correlates with most tasks, and the second factor correlates only to humor. The results thus suggest that humor is a separate skill among the other pragmatic skills. In conclusion, normative data was collected for the APACS-Heb battery, and it was found that it is a valid and reliable measure of pragmatic skills. Since APACS is a comprehensive battery assessing the various aspects of figurative language, it can identify the specific deficits in figurative language and therefore may pinpoint the appropriate intervention program for each individual.